(untitled) (Research, Society and Development, 2021)
Official data from the Brazilian National Prison Department (DEPEN) shows that Brazilian prison facilities have the fourth highest female incarcerated population in the world and intense overcrowding. With the Covid-19 pandemic being declared, the public authorities established criteria for the release by Recommendation No. 62, of March 17, 2020, edited by the National Council of Justice (CNJ). In this scenario, the study aims to analyze the condition of punitive overload by verifying the (in) effectiveness of this recommendation. From feminist and critical criminologies, within the framework of penal abolitionism, field research is carried out at the State Modulated Penitentiary of Ijuí (PMI), one of the prison institutions that make up the 3rd Penitentiary Region of Rio Grande do Sul (RS). Thus, by collecting data from criminal records and semi-structured interviews, the study specifically aims to (a) verify the level of effectiveness of the limiting rules for maintaining and decreeing prisons in the context of the pandemic; and (b) to identify the punitive burdens suffered by women deprived of their liberty, that is, the higher level of rights restrictions imposed on women compared to the rights granted to men imprisoned in the same environment, notably because the prison institution is analyzed ( masculinely) mixed. As a conclusion, it remains that staying in illegal conditions of incarceration despite the crisis is legitimized by judicial and administrative decisions.